An integrated food management framework: A preventive measure for food scarcity during the Prabowo Subianto administration - Gunawan, Cakti Indra; Suhendrik, Hendrik; Supartini, Nonok; Dyanasari, Dyanasari; Aditia, Dito; Yoga, Tirta; Cakti, Vega Raksa Cindi; Bah, Cherno (Edelweiss Applied Science and Technology, 2024)
The Food and Agriculture Organization (FAO) reported in 2024 that Indonesia is at risk of facing a future food crisis if adequate food supply is not ensured. A critical aspect of food management in Indonesia lies in its management systems. Thus, this study aims to review the extent to which food management under the Joko Widodo administration has been integrated to address food shortages. Further, this study will develop an integrated food management system as an alternative to prevent food scarcity during the Prabowo Subianto administration. The methodology involves a literature review and in-depth interviews with stakeholders involved in managing the national food reserve. Findings indicate that food management in Indonesia remains fragmented and lacks integration between central and local governments, hindering effective food management during periods of scarcity. Based on an online website, the proposed integrated food management framework aims to simplify national food management and prevent food shortages.